Interactive Museum Innovation with Digital Technology to Enhance Education and Preserve Cultural Heritage in Indonesia - Rizal, Chairul; Erni Marlina Saari (CV Raskha Media Group, 2025)
Museums play an important role in preserving cultural heritage and educating the public. However, the changing behavior of the younger generation, who are more interested in digital media, has led to a further decline in visits to traditional museums. This research aims to design a digital technology-based interactive museum prototype as an effort to enhance education and cultural preservation in Indonesia. This research method uses a Research and Development (R&D) approach, which includes the stages of needs analysis, system design, prototype development, and user testing. The research instruments include the System Usability Scale (SUS) and semi-structured interviews with 30 respondents. The research findings indicate that the interactive museum prototype achieved an average SUS score of 75.6, placing it in the excellent category, and received positive feedback regarding increased visitor engagement in understanding cultural collections. This research contributes to the development of a digital museum model that meets the needs of Indonesian society.